Green Jobs Creation – Main Element in the Implementation of Bioeconomic Mechanisms - Florin-Alexandru Luca; Gheorghe Epuran; Claudia-Ioana Ciobanu; Adrian V. Horodnic (Amfiteatru Economic)
Green jobs creation is the main element in the implementation of bioeconomy mechanisms along with other factors, such as gross domestic product (GDP), environmental protection and national security. The aim of this paper is to develop a profile of companies willing to create new jobs. Its objectives aim to identify the factors contributing to green jobs creation (objective 1) and to test the correlation of factors related to green jobs creation (objective 2). To reach the formulated objectives, the authors have used data extracted from Eurobarometer Flash 456 – SMEs, resource efficiency and green markets, representative for the 28 member states of the European Union that comprise interviews held between September 11 and 26 of 2017. For data analysis, first the descriptive methods, and then the multilevel logistic regression were used. The results show a higher likelihood that manufacturing companies with over 50 employees use personnel for green jobs, a turnover of over 500 million Euro, and an upward evolution of turnover. Novelty of the study lies in the development of an index for efficient use of resources comprising the implementation of a set of green measures that proved to be a significant instrument for new green jobs creation.